NANOBIOTECHNOLOGY IN HEALTH SCIENCES: CURRENT APPLICATIONS TO FUTURE PERSPECTIVES - ALI , A; KAMRAN , A (Biological and Clinical Sciences Research Journal, 2024)
This mini-review provides a comprehensive overview of the current applications and future perspectives of nanobiotechnology in health sciences. Drawing upon recent advancements, the review explores the role of nanoparticles in drug delivery, diagnostic imaging, therapeutics, regenerative medicine, and point-of-care diagnostics. Each application is discussed in detail, highlighting the significant contributions of nanotechnology to precision medicine, targeted therapy, bioimaging technologies, nanorobotics, and bioinformatics integration. Additionally, the review emphasizes the potential impact of nanobiotechnology on improving patient outcomes and advancing healthcare delivery. The review incorporates data from various databases, including PubMed, Web of Science, Scopus, and Google Scholar, to provide a comprehensive and up-to-date analysis of the field.